Prevalence and risk factors for type 2 diabetes mellitus in South India - S. S., Rajesh; M., Anupama; T. M., Shwetha; R., Swetha; S., Usha Rani (International Journal Of Community Medicine And Public Health, 2025)
Background: Diabetes mellitus is an iceberg disease. It has reached epidemic proportions globally. According to the World Health Organization, approximately 340 million people have diabetes mellitus worldwide. The prevalence rates have been estimated to be 12% in urban areas and 4% in rural areas. The objectives of the study were to identify the prevalence of type 2 diabetes mellitus in urban field practice area and to study risk factors for type 2 diabetes mellitus in urban field practice area. Methods: This cross-sectional study was conducted in Mangalore. The study comprised 827 subjects. A pre-tested semi-structured questionnaire was used to collect the data regarding the socio-demographic profile, personal habits, and medical history. Capillary blood glucose estimation was done by using glucometer. Statistical analysis was performed using SPSS version 16. Results: A total of 827 subjects were participated in the study. The socio-demographic characteristics of the study population showed that 390 (47.2%) were males and 437 (52.8%) were females. The overall prevalence of type 2 diabetes mellitus was 13.5%. Prevalence of diabetes was 15.6% among males and 11.7% among females. The prevalence among overweight and obese was 13.2% and 21.1% respectively. The prevalence among hypertensive subjects was 28.6%. Prevalence of diabetes among smokers was 18.6%. The prevalence of diabetes among alcohol users was 27.2%. Conclusions: The prevalence of diabetes was slightly higher in comparison to earlier studies. Hence, it is necessary to take steps to implement primary and secondary prevention of diabetes.